1996
DOI: 10.1016/s1078-5884(96)80182-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of selective patching following carotid endarterectomy

Abstract: This study suggests that patch angioplasty of larger carotid arteries may be unnecessary. Randomisation of larger arteries between patch and primary closure would be required to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
1
26
1
Order By: Relevance
“…6,8 -12,23-25 Others have suggested that the apparent benefit of patch angioplasty is most readily seen in the previously defined high-risk groups, which comprised patients with small arteries, female sex, or continued use of tobacco. 5,26 This present report suggests that patch angioplasty is beneficial to all groups since we were unable to demonstrate any specific risk factor that was associated with a higher incidence of recurrent carotid stenosis. Specifically, female sex, continued use of tobacco, and other factors, including hyperlipidemia, were not associated with an increased risk of recurrent stenosis in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…6,8 -12,23-25 Others have suggested that the apparent benefit of patch angioplasty is most readily seen in the previously defined high-risk groups, which comprised patients with small arteries, female sex, or continued use of tobacco. 5,26 This present report suggests that patch angioplasty is beneficial to all groups since we were unable to demonstrate any specific risk factor that was associated with a higher incidence of recurrent carotid stenosis. Specifically, female sex, continued use of tobacco, and other factors, including hyperlipidemia, were not associated with an increased risk of recurrent stenosis in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…Multiple comparative reviews have failed to demonstrate a consistent difference in outcomes with either technique compared with the other. [395][396][397][398][399][400][401][402][403][404][405] One report involved a single experienced surgeon and a series of patients who required staged bilateral CEA in whom 1 side was randomly allocated to primary closure and the other side to patch angioplasty. 406 Patch angioplasty was associated with lower 30-day surgical morbidity and mortality and fewer cases of residual or recurrent stenosis as assessed by periodic duplex scanning for up to 1 year postoperatively.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…The advantage of patch closure is visual confirmation of complete plaque removal, but the disadvantage is the greater length of time required for closure. Multiple comparative reviews have failed to demonstrate a consistent difference in outcomes with either technique compared with the other (395)(396)(397)(398)(399)(400)(401)(402)(403)(404)(405). One report involved a single experienced surgeon and a series of patients who required staged bilateral CEA in whom 1 side was randomly allocated to primary closure and the other side to patch angioplasty (406).…”
Section: Technical Considerationsmentioning
confidence: 99%